Virtual Research Environment for Value-Added Services in National and Regional NRENs: Case Studies - Prnjat, Ognjen; Liabotis, Ioannis; Kanellopoulos, Christos (My University, 2015)
Case studies are presented for the role of national and regional NRENs beyond connectivity, encompassing computing (grid, cloud and High-Performance computing) services and big data management services. The case studies are the recently started VI-SEEM and MAGIC projects. The VI-SEEM project, started in October 2015, unifies the existing e-Infrastructures in South-East Europe (SEE) and the Eastern Mediterranean (EM), including Grid, cloud, and High-Performance Computing resources. It does so in order to better utilise synergies, for an improved service provision within a unified Virtual Research Environment (VRE) to be provided to the scientific user communities in this large region. The overall objective is to provide a user-friendly integrated e-Infrastructure platform for scientific communities in Climatology, Life Sciences, and Cultural Heritage for the SEE and EM regions; by linking networking, computing, data, and visualization resources, as well as services, software and tools. The Virtual Research Environment provides the scientists and researchers with the support in the full lifecycle of scientific research: accessing relevant data necessary for their research, using it with provided codes and tools to carry out new experiments and simulations on large-scale e-Infrastructures, and producing and integrating new knowledge and data - which is stored and shared within the same VRE. The project is founded on the service-oriented data-driven approach, where a specific set of activities deals not just with simple e-Infrastructure data storage (live, dropbox-like), but includes the support for the full data lifecycle for the 3 target communities. The value-added computing services provided to the researchers include grid and cloud computing, as well as large-scale High-Performance Computing platforms, with a set of management tools provided for the unified management of computing resources. All project services will be provided through a service catalogue. Similarly the MAGIC project, started in May 2015, aims to adopt a service-oriented approach to advertising specifically the NREN cloud services, and this approach will be implemented through a compatible service catalogue, based on the GEANT cloud catalogue: thus the envisaged MAGIC cloud catalogue is also briefly discussed.
Keywords: Virtual Research Environment; Service catalogues; Grid computing; Cloud computing; HighPerformance computing; Data management